Comprehensive Analysis of Behavioural and Functional Traits in Dairy Sire Selection: A Review (Indian Journal of Animal Production and Management, 2024)
The comprehensive integration of  behavioural and functional traits in the selection and  breeding of dairy cattle represents a holistic  approach. The particular emphasis on behavioral  traits, particularly milking temperament, holds  significant importance for animal breeders. These  traits not only exert a notable influence on  production metrics but also contribute to the  longevity of dairy animals. Consequently, these  factors collectively impact the overall profitability  and sustainability of dairy enterprises. While  developed countries have embraced a holistic  approach in their dairy cattle selection programs,  the studies on milking temperament and milking  speed of indigenous cattle in the Indian  subcontinent remain limited. This review aims to  present existing research on the genetic  parameters of milking temperament and milking  speed in dairy cattle, with a specific focus on the  need for future strategies in studying these traits in  Indian cattle. In light of research suggesting the  pivotal role of good milking temperament and  balanced milking speed for enhanced sustainability,  it is imperative to establish a systematic recording  system with a standardized scale specifically  tailored for Indian cattle breeds. This initiative would  contribute to the overall understanding and  improvement of milking traits, fostering the  development of more effective selection criteria.
Keywords: dairy sire selection; milking temperament; behavioural traits; sustainability; Indian cattle